C‐Jun N‐terminal Kinase‐Dependent Endoplasmic Reticulum Stress Pathway is Critically Involved in Arjunic Acid Induced Apoptosis in Non‐Small Cell Lung Cancer Cells. (20th January 2016) - Joo, HyeEun; Lee, Hyun Joo; Shin, Eun Ah; Kim, Hangil; Seo, Kyeong‐Hwa; Baek, Nam‐In; Kim, Bonglee; Kim, Sung‐Hoon
Abstract : Though arjunic acid, a triterpene isolated from Terminalia arjuna, was known to have antioxidant, antiinflammatory, and cytotoxic effects, its underlying antitumor mechanism still remains unclear so far. Thus, in the present study, the molecular antitumor mechanism of arjunic acid was examined in A549 and H460 non‐small cell lung cancer (NSCLC) cells. Arjunic acid exerted cytotoxicity by 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5‐diphenyl tetrazolium bromide (MTT) assay and significantly increased sub‐G1 population in A549 and H460 cells by cell cycle analysis. Consistently, arjunic acid cleaved poly (ADP‐ribose) polymerase (PARP), activated Bax, and phosphorylation of c‐Jun N‐terminal kinases (JNK), and also attenuated the expression of pro‐caspase‐3 and Bcl‐2 in A549 and H460 cells. Furthermore, arjunic acid upregulated the expression of endoplasmic reticulum (ER) stress proteins such as IRE1 α, ATF4, p‐eIF2α, and C/EBP homologous protein (CHOP) in A549 and H460 cells. Conversely, CHOP depletion attenuated the increase of sub‐G1 population by arjunic acid, and also JNK inhibitor SP600125 blocked the cytotoxicity and upregulation of IRE1 α and CHOP induced by arjunic acid in A549 and H460 cells. Overall, our findings suggest that arjunic acid induces apoptosis in NSCLC cells via JNK mediated ER stress pathway as a potent chemotherapeutic agent for NSCLC.